ACCOUNTING AND CONTROL SYSTEM OF INFORMATION AND ANALYTICAL SUPPORT OF THE GOALS OF MANAGEMENT (UKSIAO), PRINCIPLES AND BASIS OF ITS FORMATION - S. Ponomareva (Publishing House of the State University of Management, 2018)
The study of the formation of an accounting and control system for information and analytical support of management objectives is presented. The principles and foundations of its formation for the tactical and strategic objectives of business management are defined. When forming strategically oriented financial indicators, the cost of the company’s capital takes the basic place. Based on the results of the study, it is concluded that the developed accounting and control system of information and analytical support of the company’s market value management goals and its business processes is integrated with other management systems in the mode of their parallel automation. The interconnections of all formalized systems are reduced to the creation of an organizational and functional management structure a company whose information basis is integrated accounting and quality management of business processes.